2008
DOI: 10.1111/j.1365-3148.2007.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐HBc screening in Egyptian blood donors reduces the risk of hepatitis B virus transmission

Abstract: Occult hepatitis B virus (HBV) in blood donors is considered as a potential risk for transmission of HBV infection. The aim of this study was to determine the prevalence of anti-hepatitis B core antibody (anti-HBC) positivity in Egyptian blood donations as well as to estimate the frequency of HBV-DNA in anti-HBc-positive donations. The study included 760 Egyptian healthy blood donors, representing 26 different Egyptian governorates screened according to routine practice for the presence of hepatitis B surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 30 publications
8
48
4
Order By: Relevance
“…This is comparable to the older antiHBc prevalence rates reported among HBsAg-negative blood donors in the Mediterranean region and Arab Peninsula; 15.03% in Greece [24] and 16.4% in Saudi Arabia [25] , respectively. A previous Egyptian study, however, reported a prevalence of 10.9% in volunteer HBsAgnegative blood donors, where, HBV-DNA was detected in 11.54% of the anti-HBc positive units [26] . A more recent study among Egyptian healthy male HBsAgnegative donors showed that 80/1026 (7.8%) were reactive to anti-HBc.…”
mentioning
confidence: 98%
“…This is comparable to the older antiHBc prevalence rates reported among HBsAg-negative blood donors in the Mediterranean region and Arab Peninsula; 15.03% in Greece [24] and 16.4% in Saudi Arabia [25] , respectively. A previous Egyptian study, however, reported a prevalence of 10.9% in volunteer HBsAgnegative blood donors, where, HBV-DNA was detected in 11.54% of the anti-HBc positive units [26] . A more recent study among Egyptian healthy male HBsAgnegative donors showed that 80/1026 (7.8%) were reactive to anti-HBc.…”
mentioning
confidence: 98%
“…After full-text screening, a total of 47 records were deemed as eligible papers published between 1995 and 2016. These 47 records were composed of 13 studies from Iran (4, 10-21), 8 studies from Turkey (22-29), 8 studies from Saudi Arabia (30-37), and 6 studies from Egypt (38)(39)(40)(41)(42)(43). Two studies were available from each of the following countries: Syria (44,45), Libya (46,47), Yemen (48,49), and Israel (50,51).…”
Section: Study Screening and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Occult HBV infection (OBI) was defined by an international workshop held in 2008 as the "presence of HBV DNA in liver (with a viral load of < 200 IU/mL or undetectable HBV DNA in the serum) of individuals testing hepatitis B surface antigen negative by currently available assays" (6)(7)(8). The prevalence of OBI carriers was shown to be more prominent since the introduction of HBV DNA nucleic acid testing (NAT) in blood transfusion centers across all continents with yield varying from 0.1% to 4.16% (2)(3)(4)(5)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%